PENERAPAN EDUKASI TERHADAP LANSIA PENDERITA HIPERTENSI - Witri, Witriyani; Nur Fatikatur Rohmah (Jurnal Kesehatan dan Kedokteran, 2024)
Hypertension is a chronic disease that needs to be watched out for and attacks many elderly people. This is due to unhealthy lifestyle factors, as well as lack of access to health services which can trigger other disease complications. In dealing with this problem, prevention efforts are carried out by providing health education. The aim of health education is to optimize the program for controlling and maintaining hypertension in the elderly. The main target is health cadres, where health cadres play an important role in providing education to the elderly because they have sufficient knowledge in preventing hypertension complications, and are committed to implementing recommendations given by health cadres.